New deep eutectic solvent assisted extraction of highly pure lignin from maritime pine sawdust (Pinus pinaster Ait.) - Fernandes, Catarina (2021)
Lignocellulosic biomass is a renewable and sustainable feedstock, mainly composed of cellulose, hemicellulose, and lignin. Lignin, as the most abundant natural aromatic polymer occurring on Earth, has great potential to produce value-added products. However, the isolation of highly pure lignin from biomass requires the use of efficient methods during lignocellulose fractionation. Therefore, in this work, novel acidic deep eutectic solvents (DESs) were prepared, characterized and screened for lignin extraction from maritime pine wood (Pinus pinaster Ait.) sawdust. The use of cosolvents and the development of new DES were also evaluated regarding their extraction and selectivity performance. The results show that an 1 h extraction process at 175 ?C, using a novel DES composed of lactic acid, tartaric acid and choline chloride, named Lact:Tart:ChCl, in a molar ratio of 4:1:1, allows the recovery of 95 wt% of the total lignin present in pine biomass with a purity of 89 wt%. Such superior extraction of lignin with remarkable purity using a ?green? solvent system makes this process highly appealing for future large-scale applications. ? 2021 Elsevier B.V. All rights reserved.